2021
DOI: 10.14309/ctg.0000000000000394
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Gastroenteritis: Using Presenting Findings to Predict Disease Course

Abstract: INTRODUCTION: Studies on eosinophilic gastroenteritis have identified broad spectrums of disease. We aimed to characterize subtypes of disease and ascertain outcomes of each group. METHODS: This is a retrospective cohort study from a large tertiary medical center including 35 patients diagnosed with eosinophilic gastroenteritis from 2007 to 2018. We defined 2 groups of patients based on clinical and laboratory findings at presentation. Severe disease was defined as having w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(31 reference statements)
0
6
1
Order By: Relevance
“…It is important that a comprehensive set of biopsy samples has not been obtained and that the number of biopsy samples from each site has not been standardized. Although it was reported that hypoalbuminemia could be an indicator of the necessity for maintenance therapy [27], we could not confirm it due to an insufficient amount of data on serum albumin in this study. Also, it was reported that an increasing number of involved gastrointestinal segments was associated with a recurring or continuous disease course [26].…”
Section: Color Version Available Onlinecontrasting
confidence: 57%
“…It is important that a comprehensive set of biopsy samples has not been obtained and that the number of biopsy samples from each site has not been standardized. Although it was reported that hypoalbuminemia could be an indicator of the necessity for maintenance therapy [27], we could not confirm it due to an insufficient amount of data on serum albumin in this study. Also, it was reported that an increasing number of involved gastrointestinal segments was associated with a recurring or continuous disease course [26].…”
Section: Color Version Available Onlinecontrasting
confidence: 57%
“…Pineton et al (41) reviewed files from 43 patients diagnosed with EGE who were followed from January 1988 to April 2009 and reported that 18 patients (42%; 9 with subserosal disease) had an initial flare of the disease without relapse, 16 (37%) had multiple flares that were separated by periods of full remission (recurring disease), and 9 (21%) had chronic disease. Another center reported that 18 of 35 patients with EGE, had remission without chronic symptoms, whereas 10 had chronic symptoms requiring chronic medical therapy (42). Whether these findings represent a transient innate response manifested by mucosal eosinophilia or a clinical pattern of waxing and waning non‐EoE EGIDs is uncertain.…”
Section: Statements Summary Of Evidence and Recommendationsmentioning
confidence: 99%
“…Finally, several studies have shown that some patients with non-EoE EGIDs may have waxing and waning courses, underscoring the need for longterm follow-up. Overall, the evidence to date suggests that non-EoE EGIDs have a chronic course similar to EoE, but with some important caveats (14,19,21,22,29,41,42). First, while most clinical experience and data support the fact that non-EoE EGIDs are chronic, some studies suggest that non-EoE EGIDs can resolve.…”
Section: Are Non-eoe Egids Chronic? Summary Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] Pineton de Chambrun et al [ 50 ] reported a large series of adult patients with EGE and eventually identified that the disease courses were different, with half the patients presenting with a more complex natural history characterized by unpredictable relapses and chronic courses. In another study, Havlichek et al [ 77 ] found that presence of weight loss, hypoalbuminemia, serosal disease involvement, or anemia at the time of diagnosis put the patients at a higher risk of developing a chronic course that may require long-term medication. During the initial inspection of patients, clinicians may need to pay attention to these factors to determine future medical therapy.…”
Section: Prognosismentioning
confidence: 99%